The carbon footprint of different modes of birth in the UK and the Netherlands: an exploratory study using life cycle assessment - Spil, NA; van Nieuwenhuizen, KE; Rowe, R; Thornton, JG; Murphy, E; Verheijen, E; Shelton, CL; Heazell, AEP (Wiley, 2024)
Objective: To compare the carbon footprint of caesarean and vaginal birth.